Ammonia Inhibition Level of Anaerobic Microbes Acclimated in the Anaerobic Digester Treating Pig Slurry Under the High Ammonia Nitrogen - Yoon, Young-Man; An, Jae Ho (International Journal For Research In Agricultural And Food Science, 2019)
A biochemical methane potential (BMP) assay was conducted to determine ammonia inhibition level of acclimated methanogens inoculated from an anaerobic digester in high total ammonia nitrogen (TAN) concentration. Anaerobic methane production was assessed by batch anaerobic reactor in mesophilic condition (38℃). Ammonium chloride (NH4C1) was added to adjust the TAN concentration to 1,000, 2,000, 3,000, 4,000, 5,000, 6,000, 7,000, 8,000, 9,000, 10,000 and 13,000 mg/L. The reactors of triplicate for each treatment and blank were incubated up to 50 days in a convection incubator. The biogas productions from the reactors below 7,000 mg TAN/L level were not different significantly, and the significant reduction of biogas production arose above from 8,000 mg TAN/L level. The theoretical methane potential of cellulose material, calculated by Buswell’s equation, was 0.414 Nm3/kg-VSadded. Ultimate methane potentials were in the range of 0.32-0.36 Nm3/kg-VSadded at the NH4+-N levels between 1,000 and 6,000 mg/kg. The ultimate methane potentials at the ammonia levels between 10,000 and 13,000 mg TAN/L showed the very low values of 0.10, 0.006 Nm3/kg-VSadded. Results of this study have presented that the methanogens acclimated at the high strength ammonium-nitrogen of about 4,000 – 5,000 mg/L could be tolerant to the ammonium nitrogen concentration of 7,000 mg/L. These results imply that the acclimation technology of methanogens is very useful for the improvement of digester microbial stability in the inhibitory anaerobic condition.